An Empirical Study on Instructional Leadership, School Climate and Teacher Efficacy - Arumugam Raman; Raamani Thannimalai; Iran Anak Jalapang (Journal of Pedagogy and Education Science, 2022)
The goal of this study is to evaluate how instructional leadership, teacher efficacy, and school climate influence students' academic performance. The study included 381 teachers from six divisions in Sarawak, Malaysia. This study used a cross-sectional survey approach. Questionnaires were used to collect data from respondents. For descriptive analysis, SPSS version 26.0 was utilised, while SmartPLS 3.0 was employed for partial least squares-structural equation modeling (PLS-SEM) analysis. By focusing on secondary school teachers, the paper adds new knowledge to literature. Surprisingly, the results of the investigation revealed that principals' instructional leadership and school climate had no substantial impact on student academic performance. Meanwhile, it was discovered that teacher efficacy has a considerable impact on student academic performance, implying that teacher efficacy is a predictor of student academic performance. Furthermore, teacher experience was not a significant moderator variable. Future research should focus on principals' self-assessment of instructional leadership and the moderating effect of school climate on student performance. The ramifications of the disparity between Asian instructional leadership and western literature should also be investigated.